2020
DOI: 10.1101/2020.08.30.274506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Face-to-Face to Online Modality: Implications for Undergraduate Learning While the World is Temporarily Closed in the Age of COVID-19

Abstract: The second half of the Spring 2020 semester has been an unprecedented time globally due to the ongoing coronavirus disease 2019 (COVID-19). COVID-19 pandemic has forced more than one billion students out of school, has disrupted the world and led all university courses switched to online instruction social distancing actions taken to limit the spread of the virus. The aim of the present study is to evaluate the pandemic related changes for undergraduate students, to assess their perspectives related to their l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Real-time, computer-based classroom has proved to be equally effective as the physical classroom especially when it is asynchronous Mullen (2020). About 88% of the respondents in the study by Hacisalihoglu (2020) revealed that the Covid-19 pandemic had an impact on their education, with 19% indicating a preference for online over face-to-face learning. Meanwhile, Yang et al (2020); Julien and Dookwah (2020) have noted that face-to-face learning is essential for courses such as Mathematics.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Real-time, computer-based classroom has proved to be equally effective as the physical classroom especially when it is asynchronous Mullen (2020). About 88% of the respondents in the study by Hacisalihoglu (2020) revealed that the Covid-19 pandemic had an impact on their education, with 19% indicating a preference for online over face-to-face learning. Meanwhile, Yang et al (2020); Julien and Dookwah (2020) have noted that face-to-face learning is essential for courses such as Mathematics.…”
Section: Discussion Of Resultsmentioning
confidence: 99%